2014
DOI: 10.1155/2014/127859
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Ionospheric Response to the Solar Eclipse of November 03, 2013

Abstract: The ionospheric dynamics is highly influenced by the solar radiation. During a solar eclipse, the moon occults the solar radiation from reaching the ionosphere, which may drastically affect the variability of the ionosphere. The variability of total electron content (TEC) observed by dual frequency Global Positioning System (GPS) receivers has made it possible to study effects of solar eclipse on the ionosphere. Total eclipse occurred on November 03, 2013, and the maximum amplitude was visible at Owiny in nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 17 publications
2
5
0
1
Order By: Relevance
“…The diurnal variation of TEC on the eclipse day at each station is compared with the normal trend derived from averaged TEC of the top five international Quiet days of the month and their corresponding standard errors as shown in Figure 12 12:2 NST (06:44 UT) and 12:45 NST (07:00 UT) and for the stations CHLM, JIR2, KUGE, NPGJ and SYBC respectively. Thus, the decrease in VTEC closely follows the evolutionary pattern of the eclipse, the same was earlier observed by Amabayo et al (2014); Vyas and Sunda (2012).…”
Section: Tec Variation During Eclipse Day Compared To Quiet Dayssupporting
confidence: 83%
“…The diurnal variation of TEC on the eclipse day at each station is compared with the normal trend derived from averaged TEC of the top five international Quiet days of the month and their corresponding standard errors as shown in Figure 12 12:2 NST (06:44 UT) and 12:45 NST (07:00 UT) and for the stations CHLM, JIR2, KUGE, NPGJ and SYBC respectively. Thus, the decrease in VTEC closely follows the evolutionary pattern of the eclipse, the same was earlier observed by Amabayo et al (2014); Vyas and Sunda (2012).…”
Section: Tec Variation During Eclipse Day Compared To Quiet Dayssupporting
confidence: 83%
“…The opposite is found on 1 and 3 July. Many published papers have made single quiet day comparisons (e.g., Amabayo et al, 2014; Momani et al, 2010) and may have overestimated or underestimated the ionospheric response to the moon shadow. To avoid this ambiguity, Reinisch et al (2018) compared observed eclipse variations with model variations instead.…”
Section: Discussionmentioning
confidence: 99%
“…Their principal findings are as follows: (a) vTEC declined during the eclipse compared with the values observed during seven reference days (some before and after the eclipse); (b) TEC oscillations were observed with 40-120 min periods and were associated with an AGW generated in the lower atmosphere; and (c) N(h) was reduced at all heights (10%-48%) with a maximum reduction at 360 km. Amabayo et al (2014) investigated the response of the equatorial ionosphere to the solar eclipse on 3 November 2013. Four GPS receivers over East Africa (from 2.69°to 6.73°S geomagnetic latitude) were used.…”
Section: Journal Of Geophysical Research: Space Physicsmentioning
confidence: 99%
“…During the eclipse, the F region shows a large upward drift towards the upper heights. This upward drift may also cause slowing of the diffusion and hence reduce the ionization of the F 2 region, while increase the accumulation of ionization in the F1 region, which the stratification become more prominent [29,30].…”
Section: Introductionmentioning
confidence: 99%